Monte Carlo simulation of PET images for injection dose optimization - Boldyš, Jiří; Dvořák, Jiří; Skopalová, Magdaléna; Bělohlávek, Otakar (International journal for numerical methods in biomedical engineering, 2013)
When a patient is examined by positron emission tomography (PET), radiotracer dose amount (activity) has to be determined. However, the rules for activity correction according to patients' weight used nowadays do not correspond with practical experience. Very high image quality is achieved for slim patients, whereas noisy images are produced for obese patients. There is opportunity to modify the correction rule with the aim to equalize image quality within the broad spectrum of patients and to diminish radiation risk to slim patients, with special importance for children. We have built a model of a particular PET scanner and approximated human trunk, which is our region of interest, by a cylindrical model with segments of liver, outer adipose tissue, and the rest. We have performed Monte Carlo simulations of PET imaging using the GATE simulation package. Under reasonably simplifying assumptions and for special parameters, we have developed curves that recommend amount of injected activity based on body parameters to give PET images of constant quality, the quality being expressed in terms of noise equivalent counts. The dependence qualitatively differs from the rules used in clinical practice nowadays, and the results indicate potential for improvement.
Keywords: Torso; Radiation Dosage; Tomography, X-Ray Computed; index tělesné hmotnosti; pozitronová emisní tomografie; Humans; Image Processing, Computer-Assisted; Radioactive Tracers; Computer Simulation; metoda Monte Carlo; Phantoms, Imaging; Models, Biological; Positron-Emission Tomography; radioaktivní indikátory; fantomy radiodiagnostické; Body Size; Body Mass Index; Monte Carlo Method; počítačová simulace; trup; biologické modely; počítačové zpracování obrazu; velikost těla; Drug Dosage Calculations; lidé; výpočet dávky léku; počítačová rentgenová tomografie; dávka záření